Selective Isolation of Acidophilic Streptomyces Strains for Glucose Isomerase Production - Bok, Song H. (1984)
Approximately 260 Streptomyces strains were isolated from neutral pH farmland soil and evaluated for their ability to produce glucose isomerase. The number of acidophilic Streptomyces organisms growing at pH 4.0 was low, i.e., 10(3) organisms per g of soil. All of the isolates showed glucose isomerase activity when they were grown in a medium containing d-xylose, an inducer for glucose isomerase. More than half of the strains tested developed heavy growth in 24 h, and many produced high titers of glucose isomerase after 24 h of growth in a medium buffered at pH 5.0.